Dog Breed Differences in Visual Communication with Humans - Konno, Akitsugu; Romero, Teresa; Inoue-Murayama, Miho; Saito, Atsuko; Hasegawa, Toshikazu (PloS one, 2016)
Domestic dogs (Canis familiaris) have developed a close relationship with humans through the process of domestication. In human-dog interactions, eye contact is a key element of relationship initiation and maintenance. Previous studies have suggested that canine ability to produce human-directed communicative signals is influenced by domestication history, from wolves to dogs, as well as by recent breed selection for particular working purposes. To test the genetic basis for such abilities in purebred dogs, we examined gazing behavior towards humans using two types of behavioral experiments: the 'visual contact task' and the 'unsolvable task'. A total of 125 dogs participated in the study. Based on the genetic relatedness among breeds subjects were classified into five breed groups: Ancient, Herding, Hunting, Retriever-Mastiff and Working). We found that it took longer time for Ancient breeds to make an eye-contact with humans, and that they gazed at humans for shorter periods of time than any other breed group in the unsolvable situation. Our findings suggest that spontaneous gaze behavior towards humans is associated with genetic similarity to wolves rather than with recent selective pressure to create particular working breeds.